Initial experience with stylet‐driven versus lumenless lead delivery systems for left bundle branch area pacing. (30th December 2022) - Braunstein, Eric D.; Kagan, Ruth D.; Olshan, David S.; Gabriels, James K.; Thomas, George; Ip, James E.; Markowitz, Steven M.; Lerman, Bruce B.; Liu, Christopher F.; Cheung, Jim W.
Abstract: Introduction: Left bundle branch area pacing (LBBP) has emerged as an alternative method for conduction system pacing. While initial experience with delivery systems for stylet‐driven and lumenless lead implantation for LBBP has been described, data comparing outcomes of stylet‐driven versus lumenless lead implantation for LBBP are limited. In this study, we compare success rates and outcomes of LBBP with stylet‐driven versus lumenless lead delivery systems. Methods: Eighty‐three consecutive patients (mean age 74.1 ± 11.2 years; 56 [68%] male) undergoing attempted LBBP at a single institution were identified. Cases were grouped by lead delivery systems used: stylet‐driven ( n = 53) or lumenless ( n = 30). Baseline characteristics and procedural findings were recorded and compared between the cohorts. Intermediate term follow‐up data on ventricular lead parameters were also compared. Results: Baseline characteristics were similar between groups. Successful LBBP was achieved in 77% of patients, with similar success rates between groups (76% in stylet‐driven, 80% in lumenless, p = 0.79), and rates of adjudicated LBB capture and other paced QRS parameters were also similar. Compared with the lumenless group, the stylet‐driven group had significantly shorter procedure times (90 ± 4 vs. 112 ± 31 min, p = 0.004) and fluoroscopy times (10 ± 5 vs. 15 ± 6 min, p = 0.003). Ventricular lead parameters at follow‐up were similar, and rates of procedural complications and need for lead revision were low in both groups. Conclusion: Delivery systems for stylet‐driven and for lumenless leads for LBBP have comparable acute success rates. Long‐term follow‐up of lead performance following use of the various delivery systems is warranted. Abstract : Eighty‐three patients undergoing left bundle branch area pacing (LBBP) with 53 using stylet‐driven and 30 using lumenless lead systems) were compared. Similar rates of successful LBBP were seen with similar rates of low complications. Shorter procedure and fluoroscopy times were identified in the stylet‐driven LBBP group.